If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = -6f + 8 Reorder the terms: 22 = 8 + -6f Solving 22 = 8 + -6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '6f' to each side of the equation. 22 + 6f = 8 + -6f + 6f Combine like terms: -6f + 6f = 0 22 + 6f = 8 + 0 22 + 6f = 8 Add '-22' to each side of the equation. 22 + -22 + 6f = 8 + -22 Combine like terms: 22 + -22 = 0 0 + 6f = 8 + -22 6f = 8 + -22 Combine like terms: 8 + -22 = -14 6f = -14 Divide each side by '6'. f = -2.333333333 Simplifying f = -2.333333333
| 4x^-1y^-1/-4x^2 | | x+0=4 | | 10+6g=-20 | | X^4-4x^3+2x^2-8x=0 | | 36(47-5.5x)=16(5x-9)+84.6 | | 6v-9=v | | (3x^2)-7x-4=2 | | -5x-10=0equation | | 8/32+5/8=13/16 | | -1/-8x=5/24 | | -1/8x=5/24 | | 2x-6/4=4x-3 | | 5x+32=14x+67 | | (3z-u)*(3z+5u)= | | 0.9p^2-8p+3.3=2 | | 2x-6=4x-3 | | 5[2(5x-2)-(7x-5)]=2(3x+1) | | 7x=5/9 | | 3.9x-1=2.9x | | 2(x-3)=4x-3 | | 10x^2+19x=-6 | | 36(47_5.5x)=16(x_9)+84.6 | | 2x-2+2(6x+4)=-4(x+2) | | 18x-3(x-4)=7x-10 | | y-3=4(x-1) | | y-3=14 | | x+75+82/3=80 | | n+(2n+1.7)=14 | | n+13.7=-4.8 | | Y+5x=30 | | m^2-8m+20=0 | | 9=-5x |